STUDENTS’ CHALLENGES AND STRATEGIES IN IMPROVING ENGLISH LISTENING SKILLS FOR PROFESSIONAL CONTEXTS - Irmawati, Dewi; Hustarna; Arif, Nely (JELT (Jambi-English Language Teaching), 2025)
This study aims to explore the challenges faced by students in improving their English listening skills for professional contexts and to identify the strategies they use to overcome these challenges. This study uses a qualitative approach with a phenomenological method. Eight students who have completed the Listening and Speaking for Professional Purposes course in the English Education Study Program at Jambi University became research participants. Data were collected through semi- structured interviews and analyzed using the Miles and Huberman interactive model. The results show that students face linguistic challenges, including high speaking speed, unfamiliar vocabulary, different accents, excessive use of formal language, and professional jargon. In addition, psychological factors such as anxiety, lack of focus, and stress also affect their listening ability. To overcome these challenges, students develop various adaptive strategies such as audio repetition and speed adjustment, recording and translating foreign vocabulary, overcoming excessive formal language, note-taking and keyword highlighting, emotion management, and adaptation to professional jargon. These findings indicate that effective listening and learning depend not only on linguistic aspects but also on students' ability to recognize challenges and develop appropriate strategies.